2018
DOI: 10.1002/jso.25048
|View full text |Cite
|
Sign up to set email alerts
|

Is primary sidedness a prognostic factor in patients with resected colon cancer liver metastases (CLM)?

Abstract: Sidedness do not seem to be a predictor of long term survival in patients with resected colon cancer liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…For example, a number of studies have demonstrated inferior oncological outcome in patients undergoing surgical resection of CRCLM with right-sided versus left-sided colonic primary tumours[ 8 - 10 ]. This has not been a consistent observation, and others have shown no clear association[ 11 , 12 ]. The aim of the present systematic review is to provide a summary of the available evidence on the impact of PTL on oncological outcomes in patients with CRCLM.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, a number of studies have demonstrated inferior oncological outcome in patients undergoing surgical resection of CRCLM with right-sided versus left-sided colonic primary tumours[ 8 - 10 ]. This has not been a consistent observation, and others have shown no clear association[ 11 , 12 ]. The aim of the present systematic review is to provide a summary of the available evidence on the impact of PTL on oncological outcomes in patients with CRCLM.…”
Section: Introductionmentioning
confidence: 79%
“…This finding is supported by Yamashita et al[ 26 ] found that r -CRCLM were independently associated with “minor pathological response” (defined as cancer cells accounting for ≥ 50% of residual cells), and were thus less sensitive to chemotherapy with worse RFS and OS. Interestingly, Marques et al[ 11 ] found that when selecting patients for CRCLM resection based on chemosensitivity, the survival disadvantage seen with r -CRCLM was eliminated. This suggests fundamental differences in tumour biology with the less chemosensitive phenotype more frequently seen with right-sided PTL and in turn associated with poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Adam et al 30 Umeda et al 31 Huang et al 32 Mavros et al 33 Viganò et al 34 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Norén et al 38 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Dupré et al 41 Liang et al 43 Rhu et al 44 Sultana et al 45 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 Engstrand et al 50 Goffredo et al 51 lmai et al 52 Koch et al 53 Laengle et al 54 Ledys et al 55 Liao et al 56 Lionti et al 57 Loosen et al 58 Makowiec et al 59 Margonis et al 60 Marques et al 24 Oshi et al 61 Palkovics et al 62 Shigematsu et al 63 Vallance et al 64 Wang et al 23 Wang et al 65 Zheng et al 66 Prediction interval 0·1 0 ·5 1 2 10…”
Section: Fig 2 Forest Plots Showing Impact Of Primary Tumour Locatiomentioning
confidence: 99%
“…Partelli et al 29 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Heise et al 42 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 lmai et al 52 Laengle et al 54 Ledys et al 55 Lionti et al 57 Margonis et al 60 Marques et al 24 Oshi et al 61 Shigematsu et al 63 Wang et al 23 Zheng et al 66…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation